Untargeted metabolomics reveals multiple metabolites influencing smoking-related DNA methylation. (12th March 2018) - Huang, Yunfeng; Hui, Qin; Walker, Douglas I; Uppal, Karan; Goldberg, Jack; Jones, Dean P; Vaccarino, Viola; Sun, Yan V
Aim: We conducted a joint metabolomic–epigenomic study to identify patterns of epigenetic associations with smoking-related metabolites.Patients & methods: We performed an untargeted metabolome-wide association study of smoking and epigenome-wide association studies of smoking-related metabolites among 180 male twins. We examined the patterns of epigenetic association linked to smoking-related metabolites using hierarchical clustering.Results: Among 12 annotated smoking-related metabolites identified from a metabolome-wide association study, we observed significant hypomethylation associated with increased level of N-acetylpyrrolidine, cotinine, 5-hydroxycotinine and nicotine and hypermethylation associated with increased level of 8-oxoguanine. Hierarchical clustering revealed common and unique epigenetic–metabolic associations related to smoking.Conclusion: Our study suggested that a joint metabolome–epigenome approach can reveal additional details in molecular responses to the environmental exposure to understand disease risk.